(3fHPI ef GdJQGLes - (3eLghds; (3YeQ Hf eMeO Hf eMeO GdbQTj GdgGTej Gdecj, fLe GdOjf , GHf agO,J (B885 (3g` s ((3eMeO Hf eMeO Hf CHj TQja s)
(3ChdgG (B:s
(3CeG HYO , agPg fHPI ef JQGLe CTjGNfG ef fbdI GdMOjK, EfJgjfG ef eYLe LeYg UGMHfG GdTjN SQGL GdOjf eMeO GdeOYh YeQ Hf eMeO Hf eMeO s
(3BNQgG (B:s
(3heGJ ai fUa UaQ SfI (B852 (3g` ced eG GfJNHJg ef eTjNI TjNfG ddTjN CHj GdaJM GdYKeGfj s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdYGTQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B318s
Keywords: (3GdJGQjNs